Educational Video Media to Increased Knowledge and Attitude of the Elderly about Gout - Junita Marta Mbadhi; Ribka Limbu; Enjelita M Ndoen (Journal of Health and Behavioral Science, 2022)
One of the causes of gout is the intake of protein that contains purines that are too high. Efforts that can be made to prevent and minimize the risk of gout in the elderly are health education by selecting and using media that can attract interest and achieve the expected output such as video media. The study was conducted to determine the effect of counseling using video media on increasing knowledge and changing attitudes of the elderly about gout in the working area of ​​the Rukun Lima Health Center, Ende Regency in 2021. The research design used was a pre-experimental method with the method one group pretest posttest design. The study population was all elderly people with gout with the category of secondary gout aged 55-90 years with a total of 75 people. The results showed that there was a significant effect of counseling using video media with increasing knowledge and changing attitudes of the elderly about gout (ρ-value = 0.000). Video media can be used as a choice of health media in health education and promotion efforts for the community.